2022
DOI: 10.7759/cureus.21413
|View full text |Cite
|
Sign up to set email alerts
|

Study of Disease Severity and Outcomes in COVID-19 Patients With Chronic Kidney Disease at a Tertiary Care Hospital in South India

Abstract: Background: Coronavirus disease 2019 (COVID-19) disproportionately affects individuals with various comorbidities. Among these, chronic kidney disease (CKD) has been shown to be strongly associated with the progression to severe disease. This study aimed to assess the severity and disease outcomes in patients with COVID-19 infection and CKD. Methods: This is a retrospective study conducted at a tertiary care hospital from July 2021 to September 2021. The case records of patients with CKD and COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…SARS-CoV-2 використовує саме рецептор АПФ-2 для входу в клітину і агресивніший варіант Delta, що містить багато мутацій в субодиниці S 1 , поліпшує його здатність зв'язуватися з АПФ-2 [11]. Можливо, це пояснює різ-ницю у більшій частоті захворюваності на SARS-CoV-2 у світі у чоловіків, так само як і їхньої смертності [12] Встановлений у дослідженні BIRCOV феномен зниження АТ, можливо, через «ефект БРА» від SARS-CoV-2, важливо розглянути в аспекті летальності при SARS-CoV-2. Показово, що SARS-CoV-2, забезпечуючи ефект подвійної блокади РААС у людей, які отримують іАПФ або ПІР, не посилює гіпотензивного ефекту у тих, хто приймає БРА.…”
Section: обговоренняunclassified
“…SARS-CoV-2 використовує саме рецептор АПФ-2 для входу в клітину і агресивніший варіант Delta, що містить багато мутацій в субодиниці S 1 , поліпшує його здатність зв'язуватися з АПФ-2 [11]. Можливо, це пояснює різ-ницю у більшій частоті захворюваності на SARS-CoV-2 у світі у чоловіків, так само як і їхньої смертності [12] Встановлений у дослідженні BIRCOV феномен зниження АТ, можливо, через «ефект БРА» від SARS-CoV-2, важливо розглянути в аспекті летальності при SARS-CoV-2. Показово, що SARS-CoV-2, забезпечуючи ефект подвійної блокади РААС у людей, які отримують іАПФ або ПІР, не посилює гіпотензивного ефекту у тих, хто приймає БРА.…”
Section: обговоренняunclassified
“…15 A retrospective study from India indicated that 47.5 severity of COVID-19 in the non-kidney transplant patient group (47.5%) had severe COVID-19. 16 These differences could be due to sample size, study area, and study design.…”
Section: Factors Associated With Covid-19 Severitymentioning
confidence: 99%
“…Diverse factors contribute to thyroid problems in patients with CKD. CKD patients have a greater prevalence of hypothyroidism than the overall population [5] . Through the action of isoform D1 of the enzyme T4-5′-deiodinase, the kidney contributes to the synthesis of serum free triiodothyronine (FT3) by deiodinating free thyroxine (FT4).…”
Section: Introductionmentioning
confidence: 99%